(untitled) (Research, Society and Development, 2024)
The objective of this study is to evaluate the efficacy of saliva as an alternative sample for detecting SARS-CoV-2 in healthcare professionals and patients treated at a university hospital in the city of João Pessoa, in the state of Paraíba, by comparing the results with samples collected by nasopharyngeal swab (NPS). The study recruited 365 adult participants who were asymptomatic for COVID-19. Reverse transcription real-time polymerase chain reaction (RT-qPCR) targeting the E gene of SARS-CoV-2 was performed. For statistical analyses, SPSS software was used. The agreement between the two methods was assessed using the Kappa test. Of the 365 samples analyzed, 45 (12.3%) showed detection in at least one type of sample. In NPS and saliva, 21 samples (46.7%) were positive, while 14 samples (31.1%) were positive only for NPS and 10 samples (22.2%) were positive only in saliva. Using NPS samples as the reference gold standard, the sensitivity and specificity of saliva were 60% and 97%, respectively, while the positive and negative predictive values were 68% and 96%, respectively. The accuracy was 93.0%, and the Kappa coefficient was 0.596, indicating moderate agreement. Although the Kappa coefficient indicated moderate agreement in this study, pure saliva samples were similar to those obtained by NPS. The simplicity of collection, the scarcity of PPE, and the transmissibility of the virus favor self-collection of saliva as a more accurate test, leading to a reduction in wait times and faster availability of results.